Telecare mobile application - Sambadzi, Blessing (Midlands State University, 2019)
Telecare mobile application is an android based application that seeks to address the shortfalls of the USSD platform. The USSD platform have no facility for user policy switching, recommendation and grievance airing, claim posting and alerts for overdue policy payments. To solve the problems that Telecare service are facing a mobile application was proposed. Development alternatives were discussed amongst them are outsourcing, improvement and in-house development. In-house development was chosen as the best alternative. Questionnaires, interviews and observations were used as the data collection methodology and they provided enough data to show that the facilities of the mobile application were lacking. With the data at hand the feasibility to developed was done again to know if it was realistic to develop what the users asked for in the interview and questionnaires. Using the outcomes from feasibility and data analysis the coding of the proposed system took place. Coding was done using java and android studio. Implementation strategies were discussed giving preference to parallel implementation since the mobile application is not there to substitute the USSD but it complement the USSD. Maintenance of the system options were evaluated giving the perfective maintenance option since the system will be thriving through the use recommendation. For the future there is need to create a cross platform application that serve all with smartphones and also the integration of Telecash.